Case report: therapeutic monitoring of vancomycin in an acute liver failure patient with anuria under high-flow continuous hemodiafiltration - Yuriko Ito; Junya Nakade; Akihiro Seki; Ryosuke Gabata; Mitsuyoshi Okazaki; Shinichi Nakanuma; Arimi Fujita; Tsutomu Shimada; Taro Yamashita; Shintaro Yagi; Takumi Taniguchi; Yoshimichi Sai (BMC, 2023)
Abstract Background High-flow continuous hemodiafiltration (HF-CHDF) combines diffusive and convective solute removal and is employed for artificial liver adjuvant therapy. However, there is no report on dosage planning of vancomycin (VCM) in patients with acute liver failure under HF-CHDF. Case presentation A 20-year-old woman (154 cm tall, weighing 50 kg) was transferred to the intensive care unit (ICU) with acute liver failure associated with autoimmune liver disease. On the following day, HF-CHDF was started due to elevated plasma ammonia concentration. On ICU day 8, VCM was started for suspected pneumonia and meningitis (30 mg/kg loading dose, then 20 mg/kg every 12 hrs). However, on ICU day 10, VCM blood concentration was under the limit of detection (< 3.0 μg/mL) and the patient developed anuria. The VCM dose was increased to 20 mg/kg every 6 hrs. Calculation with a one-compartment model using the HF-CHDF blood flow rate as a surrogate for VCM clearance, together with hematocrit and protein binding ratio, predicted a trough VCM blood concentration of 15 μg/mL. The observed concentration was about 12 μg/mL. The difference may represent non-HF-CHDF clearance. Finally, living donor liver transplantation was performed. Conclusion We report an acute liver failure patient with anuria under HF-CHDF in whom VCM administration failed to produce an effective blood concentration, likely due to HF-CHDF-enhanced clearance. VCM dosage adjustment proved successful, and was confirmed by calculation using a one-compartment model.